Primitive Helicorbitoides (Foraminifera) and associated larger benthic foraminifera from the Campanian Tonya Formation, Trabzon, eastern Pontides, NE Turkey. (September 2019) - Özcan, Ercan; van Gorsel, J.T.; Sarı, Bilal; Yücel, Ali Osman; Erbay, Sadıkcan; Okay, Aral I.
Abstract: The genus Helicorbitoides MacGillavry represents an evolutionary stage in the transition of rotaloidean with primary spiral chambers to the forms displaying an orbitoidal-type growth pattern in the Campanian. Unlike the widespread distribution of its possible ancestor Pseudosiderolites (Douvillé) and its descendant Lepidorbitoides Silvestri, Helicorbitoides was reported from only a few localities in Europe and Turkey (Western Tethys). The genus has been previously subdivided into two evolutionary stages, H. voigti van Gorsel and H. longispiralis (Papp and Küpper) based on quantitative and qualitative test parameters. We here introduce a primitive developmental stage of Helicorbitoides by studying a new population from a calciturbidite bed of the Campanian Tonya Formation in NW Turkey. This provides the first biometric data of the genus from this part of the Tethys. The Helicorbitoides specimens, with thick robust lenticular tests, possess a low trochospiral to planispiral primary spiral of chambers that reach up to the periphery of the test, and 'orbitoidal-type' chamberlets (secondary chamberlets) between the whorls and on the wall of the last whorl. The secondary chamberlets, however, never form complete cycles. In axial sections, the lateral chambers are dense and occupy both the axial and the lateral sides of the whorls. The number of primary spiral chambers with a single stolon varies between 8 and 12 (with an average of 9.63). According to previously proposed species limits, our population is assigned to an advanced developmental stage of H. voigti, and represents a transitional developmental stage between two successive species ( H. voigti-longispiralis ). The associated orbitoidids belong to Orbitoides medius, with an embryo size (Li + li) ranging from 370 to 800 μm (with an average of 525.4 μm). The number of epi-embryonic chambers (E) varies between 4 and 6 (with an average of 4.5). Pseudosiderolites vidali is the only siderolitid genus in the studied sample. The age of the turbidite bed is considered as early late Campanian (referable to the Radotruncana calcarata Zone) or slightly older (' Inoceramus ' tenuilineatus Zone) based on the previous records of planktonic foraminifera and inoceramids from the same section and the occurrence of Pseudosiderolites vidali .